Solução analítica do potencial de Morse em mecânica clássica - Barboza, F.L. Moraes [UNESP]; Costa, A. J. [UNESP]; Ribeiro, N. F. [UNESP]; Filho, Elso Drigo [UNESP] (My University, 2007)
Usually the Morse potential is studied in the quantum mechanics context. On the other hand, there are relatively few applications for classical problems. In this work, a complete solution for the classical equation of motion is found for a particle subject to this potential. Numerical examples are presented for a fixed set of parameters. Copyright by the Sociedade Brasileira de Física.
Analytical solution of the Morse potential in classical mechanics
Keywords: Classical mechanics; Morse potential; Motion equation